1989
DOI: 10.1007/bf02624141
|View full text |Cite
|
Sign up to set email alerts
|

5′-nucleotidase activity in cultured cell lines. Effect of different assay conditions and correlation with cell proliferation

Abstract: The 5-AMPase activity of the ectoenzyme 5-nucleotidase has been measured in a variety of cell lines, using intact cells. Human cell types showed two orders of magnitude higher enzyme activity than mouse cell lines. The ectoenzyme is inhibited by adenosine 5-(alpha, beta-methylene) diphosphate and Concanavalin A. A different extent of 5-nucleotidase lectin inhibition was observed in the studied cell lines, suggesting that the corresponding ectoenzymes are glycoproteins with a different type or degree, or both, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Ecto-5'-nucleotidase is expressed or its expression is increased in cells during the process of maturation, migration or growth. This was documented for a variety of tissues and cellular systems (DePierre & Karnovsky, 1974a,b;Rodan et al, 1977;Uusitalo & Karnovsky, 1977;Dornand et al, 1986;Turnay et al, 1989) as well as for numerous tumours (Stefanovic et al, 1976;Carraway et al, 1979;Mescher et al, 1981;Amano et al, 1983;Slakey, 1985;Haffner et al, 1988;Kruger et al, 1991).…”
Section: Maturation-dependent Expressionmentioning
confidence: 88%
“…Ecto-5'-nucleotidase is expressed or its expression is increased in cells during the process of maturation, migration or growth. This was documented for a variety of tissues and cellular systems (DePierre & Karnovsky, 1974a,b;Rodan et al, 1977;Uusitalo & Karnovsky, 1977;Dornand et al, 1986;Turnay et al, 1989) as well as for numerous tumours (Stefanovic et al, 1976;Carraway et al, 1979;Mescher et al, 1981;Amano et al, 1983;Slakey, 1985;Haffner et al, 1988;Kruger et al, 1991).…”
Section: Maturation-dependent Expressionmentioning
confidence: 88%
“…It has been demonstrated that cells subjected to scratch wound increase cell proliferation ( Lampugnani, 1999 ; Kornyei et al, 2000 ), whereas the cell proliferation positively correlates with CD73 expression in many different tumor cell lines, including glioma ( Turnay et al, 1989 ; Christensen et al, 1996 ; Ciccarelli et al, 2000 ; Ohana et al, 2001 ; Bavaresco et al, 2008 ; Gao et al, 2017 ). Cell proliferation and CD73 expression are interconnected through TCF/LEF binding site in the regulatory region of CD73 gene, which is the nuclear target of Wnt pathway ( Synnestvedt et al, 2002 ; Spychala and Kitajewski, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that adenosine itself stimulates 5hnucleotidase in rat mesangial cells [39]. In different cells its activity increases during the exponential growth phase of the cells in culture and is significantly down-regulated once the cells reach confluency [40].…”
Section: Discussionmentioning
confidence: 99%